Reducing the Emotionality of Auditory Hallucination Memories in Patients Suffering From Auditory Hallucinations - Matthijssen, Suzy Johanna Martina Adriana; Heitland, Ivo; Verhoeven, Liselotte C. M.; van den Hout, Marcel A. (Frontiers in Psychiatry, 2019)
Eye Movement Desensitization and Reprocessing (EMDR) therapy targets emotionally disturbing visual memories of traumatic life events, and may be deployed as an efficacious treatment for posttraumatic stress disorder. A key element of EMDR therapy is recalling an emotionally disturbing visual memory whilst simultaneously performing a dual task. Previous studies have shown that auditory emotional memories may also become less emotional as a consequence of dual tasking. This is potentially beneficial for psychotic patients suffering from disturbing emotional auditory memories of auditory hallucinations. The present study examined whether and to what extent emotionality of auditory hallucination memories could be reduced by dual tasking. The study also assessed whether a modality matching dual task (recall + auditory taxation) could be more effective than a cross modal dual task (recall + visual taxation). Thirty-six patients suffering from auditory hallucinations were asked to recall an emotionally disturbing auditory memory related to an auditory hallucination, to rate emotionality of the memory and to recall it under three conditions: two active conditions, i.e. visual taxation (making eye-movements) or auditory taxation (counting aloud) and one control condition (staring at a non-moving dot) counterbalanced in order. Patients re-rated emotionality of the memory after each condition. Results show the memory emotionality of auditory hallucinations was reduced and the active conditions showed stronger effects than the control condition. No modality-specific effect was found: the active conditions had an equal effect.